2022
DOI: 10.1063/5.0088020
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of tunnel magnetoresistance in serial magnetic tunnel junctions

Abstract: Magnetic tunnel junctions have been widely used in various applications, such as magnetic sensors and magnetic random-access memories. In the practical application of MTJs, they are usually used in series toward high sensitivity and high stability, especially for sensor applications. In this paper, serial MTJs devices on 8 in. wafers were fabricated. The temperature dependence of the tunnel magnetoresistance ratio, resistances in parallel and antiparallel configurations, and dynamic conductance were systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Unfortunately, as we move towards higher energies, the ratio of the A PC /A APC gets reduced (figure B1(a)), which in turn declines the TMR%. Although earlier works have ascribed the TMR roll-off with temperature to the magnons [65,[67][68][69], the same can also be explained by the analysis of the spin-dependent transmission spectra within the FW. The TMR of the Nu-SLTJs exhibits notable robustness to temperature variations.…”
Section: Temperature Dependence Of the Tmr Of The Nu-sltjsmentioning
confidence: 95%
See 1 more Smart Citation
“…Unfortunately, as we move towards higher energies, the ratio of the A PC /A APC gets reduced (figure B1(a)), which in turn declines the TMR%. Although earlier works have ascribed the TMR roll-off with temperature to the magnons [65,[67][68][69], the same can also be explained by the analysis of the spin-dependent transmission spectra within the FW. The TMR of the Nu-SLTJs exhibits notable robustness to temperature variations.…”
Section: Temperature Dependence Of the Tmr Of The Nu-sltjsmentioning
confidence: 95%
“…The TMR of a CoFeB/MgO/CoFeB-based MTJ has typically been observed to show a monotonic decline with the temperature [65,66]. In figure 17 we have shown the TMR dependence of the Nu-SLTJs in reference to a typical MTJ.…”
Section: Temperature Dependence Of the Tmr Of The Nu-sltjsmentioning
confidence: 95%
“…Zhao, et al observed a decrease of TMR ratio from 150 to 105% with the increasing temperature of 10 to 400 K. 62 Two effects can be used to explain this finding. There is more magnetic disorder when the temperature goes up, which makes R AP go down and R P go up.…”
Section: Tmr Overviewmentioning
confidence: 97%